Activity of Horseshoe Leaf Extract (Ipomoea pescaprae L.) As Analgesic and Antipyretic in Mice (Mus musculus) - Sainal Edi Kamal; Firmansyah Firmansyah; Rusli Rusli; Gerfan Patandung (Politeknik Sandi Karsa, 2021)
Analgesics or painkillers are substances that reduce or eliminate pain without losing consciousness (in contrast to general anesthetics while antipyretics are drugs or substances that can reduce body temperature in a feverish state. This study aims to determine the activity of leaf extracts Tapak Kuda (Ipomoea pescaprae L.) as an analgesic and antipyretic in mice (Mus musculus) and to determine the dose of ethanol extract of Tapak Kuda leaf which has analgesic and antipyretic effects. The method used was sample extraction by maceration using 96% ethanol solvent and extract The results obtained were divided into 3 concentrations, namely 100, 300, and 500 mg/kgBW mice, then paracetamol was used in the positive control group. In the analgesic study, acetic acid was used as a pain inducer and in the antipyretic study, 10% peptone was used as a fever inducer. Male mice 15 adults used g were divided into 5 groups and each group consisted of 3 tails. Group I was treated with 1% Na-CMC as a negative control. Group II positive control of paracetamol with treatment given orally at a dose of 1 ml/30 grams of body weight to mice. Groups III, IV, and V as the test group were given ethanol extract of the leaves of Tapak Kuda (Ipomoea pescaprae L.) with extract doses of 100, 300 and 500 mg/kg BW with a volume of 1 ml / 30 gram BW. The results showed that in the analgesic test the administration of the ethanol extract of the leaves of Tapak Kuda (Ipomoea pescaprae L.) with extract doses of 300 mg/kgBW and 500 mg/kgBW could provide an analgesic effect, while the results of the antipyretic test on the administration of the ethanolic extract of the leaves of Tapak Kuda (Ipomoea pescaprae L.) with extract doses of 100, 300, and 500 mg/kgBW also had antipyretic effects.